2021
DOI: 10.3389/fnagi.2021.727417
|View full text |Cite
|
Sign up to set email alerts
|

Burning Fog: Cognitive Impairment in Burning Mouth Syndrome

Abstract: Background: Due to its common association with chronic pain experience, cognitive impairment (CI) has never been evaluated in patients with burning mouth syndrome (BMS). The purpose of this study is to assess the prevalence of CI in patients with BMS and to evaluate its relationship with potential predictors such as pain, mood disorders, blood biomarkers, and white matter changes (WMCs).Methods: A case-control study was conducted by enrolling 40 patients with BMS and an equal number of healthy controls matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 112 publications
(155 reference statements)
1
25
0
Order By: Relevance
“…In this study, pain was described by all the patients as burning in quality and it was considered the worst symptom by 23 (57%). The most frequent additional symptoms reported by our samples were xerostomia, a change in the tongue morphology and dysgeusia, in line with previous studies 3,33,35 . In addition, the BMS patients suffered from a high pain intensity (VAS: 8–10; BPI intensity: 19.8–30), which deeply interfered, in terms of intensity and quality, in the individual's life activities (BPI interference: 9–32).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, pain was described by all the patients as burning in quality and it was considered the worst symptom by 23 (57%). The most frequent additional symptoms reported by our samples were xerostomia, a change in the tongue morphology and dysgeusia, in line with previous studies 3,33,35 . In addition, the BMS patients suffered from a high pain intensity (VAS: 8–10; BPI intensity: 19.8–30), which deeply interfered, in terms of intensity and quality, in the individual's life activities (BPI interference: 9–32).…”
Section: Discussionsupporting
confidence: 90%
“…The most frequent additional symptoms reported by our samples were xerostomia, a change in the tongue morphology and dysgeusia, in line with previous studies. 3,33,35 Instead, in this study, from the analysis of the pain quality, the median and IQR of the SF-MPQ assessment was 5 [3-7.25] in the BMS patients, a result considered to be elevated, as compared with the study of Riordain 8 on 32 individuals, who found a median and IQR for the SF-MPQ of 1.0 [0.0-2.0], and with the study of Tu et al 36 on 248 patients, where the mean of the SF-MPQ was 2.58 ± 2.98.…”
Section: Ta B L E 5 (Continued)mentioning
confidence: 99%
“…Burning Mouth Syndrome is a type of complex chronic neuropathic orofacial pain disorder, frequently associated with emotional and cognitive impairment ( de Souza et al, 2012 ; Canfora et al, 2021 ). It is known that changes involving the brain structure and networks, typical of central neuropathies, play a key role in the aetiopathogenesis of disease ( Khan et al, 2014 ; Wada et al, 2017 ; Kurokawa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one of our previous studies, we have demonstrated for the first time that patients with BMS suffer from cognitive decline mainly in attention, working memory and executive functions, showing a higher score on the ARWMCs in the temporal lobes compared with healthy subjects, thereby suggesting a higher percentage of WMHs in this area of the brain in patients affected by BMS ( Canfora et al, 2021 ).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation